Eficiência de utilização de nutrientes por cultivares de batata - Fernandes, Adalton Mazetti [UNESP]; Soratto, Rogério Peres [UNESP] (My University, 2013)
The use of cultivars efficient in nutrient use is essential to increase yield and reduce production costs. The objective of this study was to evaluate absorption and nutrients use efficiency on five potato cultivars. The experiment was conduced in Itaí, São Paulo State, Brazil, in winter cropping season of 2008 on Oxisol. The experimental design was randomized blocks with split-plots and four replications. Plots comprised the five potato cultivars and subplots were established by sampling times, performed at planting and every seven days after emergence. At 97 DAP was calculated the nutrients use efficiency for dry matter production and at 122 DAP were calculated the nutrients use efficiency for fresh tuber and tuber dry matter yield. Mondial and Asterix cultivars showed greater dry matter production, higher fresh tubers yield and nutrients accumulation. Nutrients use efficiency for total dry matter and tubers dry matter, was similar among cultivars, but Ágata was more efficient in nutrients use efficiency for fresh tubers yield.

O uso de cultivares eficientes na utilização de nutrientes é fundamental para aumentar a produtividade e reduzir os custos de produção. Objetivou-se com esse experimento avaliar a absorção e a eficiência de utilização de nutrientes em cinco cultivares de batata. O experimento foi conduzido na safra de inverno de 2008, em Latossolo Vermelho, no município de Itaí-SP. Utilizou-se delineamento em blocos ao acaso, em esquema de parcela subdividida, com quatro repetições. As parcelas foram constituídas pelas cinco cultivares e as subparcelas por épocas de coletas, realizadas no momento do plantio e a cada sete dias após a emergência. Aos 97 dias após o plantio (DAP) calculou-se a eficiência de utilização de nutrientes para produção de matéria seca (MS) total e aos 122 DAP calcularam-se as eficiências de utilização de nutrientes para produção de tubérculos frescos e de MS dos mesmos. As cultivares Asterix e Mondial apresentaram maior produção de MS, produtividade de tubérculos frescos e maior acúmulo de nutrientes. A eficiência de utilização de nutrientes para a produção de MS total e MS de tubérculos foi semelhante entre as cultivares, mas, a cultivar Ágata foi mais eficiente na utilização de nutrientes para a produção de tubérculos frescos.
Absorption and nutrients use efficiency by potato cultivars
Keywords: Absorption; Metabolism; Mineral nutrition; Solanum tuberosum